Neuroeducation in the classroom - Flórez Centeno, Diana Fidelia (Rastros Rostros, 2024)
The present study seeks to establish the way in which neuroeducation can be used in classroom activities through a documentary review. Where it was found that early childhood is a fundamental stage of human development and, therefore, the Ministry of Education has given high priority to children from their conception to their first years of life. At this time, the brain undergoes an irreversible transformation. For it to grow and develop, going through sensitive moments for the acquisition of certain specific learning, millions of phenomenal neural connections are created. For this reason, it requires that external stimuli be of high quality, allowing children to live experiences according to each need, using physical resources and multisensory tools. It is crucial to understand that the brain develops properly considering the harmonious interaction between genetics and environmental cues. For this reason, the experiences lived by children are crucial because they allow the brain development process to be adjusted, resulting in positive or negative outcomes depending on whether adults are present in children’s lives.